Spatial mobility and occupational status attainment in the transition from school to work in Germany - Wicht, Alexandra [Verfassser]; Protsch, Paula [Verfassser]; Menze, Laura [Verfassser]; Weßling, Katarina [Verfassser] (My University, 2026)
“This study investigates opportunities for occupational status attainment through spatial mobility in early stratification processes. We focus in particular on how this relationship is conditioned by young people’s occupational status aspirations as well as by institutional and local structural opportunities, thereby scrutinizing how spatial mobility may contribute to unequal career opportunities. Empirically, we analyze occupational status attainment in the transition from school to Vocational Education and Training (VET) in Germany. Using longitudinal data from the German National Educational Panel Study (NEPS) combined with fine-grained regional information, we show that young people who commute or relocate for a VET position are more likely to secure higher-status VET positions. Yet spatial mobility is only associated with higher occupational status attainment among young people with higher levels of occupational status aspirations, among those originating from structurally weak regions, and among those with at least intermediate secondary school-leaving certificates. We conclude that spatial mobility can enable young people to overcome regional disadvantages, functioning as an agentic strategy for pursuing occupational goals more effectively. At the same time, it tends to widen status differentials between socially stratified educational groups and remains shaped by local structural opportunities.“ (authors’ abstract; BIBB-Doku)
Keywords: G 1.3.2.2 Übergänge; G 2.4.1 Bildungs- und Berufswege; G 1.3.3.3 Mobilität; 370; Jugendlicher; Berufseinmündung; Erste Schwelle; Berufswegplanung; Beruflicher Status; Einflussfaktor; Regionale Mobilität; Mobilitätsbereitschaft; Ausbildungsmobilität; Nationales Bildungspanel; Learning Analytics